Policy instruments, subsidies and value of agricultural production: Mexico, Brazil and Chile - Olvera-Avendaño, Aminta; Martínez-Bautista, Humberto; Salas-González, José María; Zavala-Pineda, María Jesica; Sagarnaga-Villegas, Leticia Myriam (Revista Mexicana de Ciencias Agrícolas, 2024)
Transfers, in the form of subsidies, are a government intervention aimed at boosting economic development. These are provided through various instruments that affect production and trade. The Organisation for Economic Co-operation and Development classifies these instruments into categories from most to least distorting. In its strategy of deregulating the world market, it encourages the use of the latter in agricultural policy. Nonetheless, the effect of this recommendation on the value of agricultural production has been poorly researched. This work assessed the relationship between the amounts of support in different agricultural policy instruments used and the value of the production of subsidized agricultural products (VpS) in Mexico, Brazil, and Chile during the period 1995-2020, through a multiple linear regression model with the stepwise backward elimination procedure. The results show that the transfer items that were relevant to explain the VpS in Mexico were: storage, marketing and other physical infrastructure, support based on area and number of animals, extension services, safety and inspection of agricultural products and institutional infrastructure (p< 0.05), in Brazil they were: research, market prices and education (p< 0.05) and in Chile they were: research, storage, marketing and other physical infrastructure, and farm restructuring (p< 0.05). It should be noted that all instruments with a significant effect on the VpS are classified as less distortive, except for the market price support present in Brazil.